2000
DOI: 10.1177/002215540004800707
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Histamine N-Methyltransferase in Guinea Pig Tissues

Abstract: Histamine plays important roles in gastric acid secretion, inflammation, and allergic response. Histamine N-methyltransferase (HMT; EC 2.1.1.8) is crucial to the inactivation of histamine in tissues. In this study we investigated the immunohistochemical localization of this enzyme in guinea pig tissues using a rabbit polyclonal antibody against bovine HMT. The specificity of the antibody for guinea pig HMT was confirmed by Western blotting and the lack of any staining using antiserum preabsorbed with purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 34 publications
4
9
0
Order By: Relevance
“…3C). Using a rabbit polyclonal antibody against purified bovine HMT, Tahara et al (15) showed strong immunoreactivity in almost the same localization as that in the present study, suggesting that HMT has a crucial role in the jejunum. In guinea pig stomach, lung and spleen, the 1.6-kb transcript was also observed (Fig.…”
supporting
confidence: 86%
“…3C). Using a rabbit polyclonal antibody against purified bovine HMT, Tahara et al (15) showed strong immunoreactivity in almost the same localization as that in the present study, suggesting that HMT has a crucial role in the jejunum. In guinea pig stomach, lung and spleen, the 1.6-kb transcript was also observed (Fig.…”
supporting
confidence: 86%
“…Conversely, HNMT is a cytosolic enzyme that is responsible for inactivation of intracellular histamine [1]. Analysis of the cellular localisation of HNMT in guinea-pig tissues, using immunohistochemical staining, revealed a widespread and diverse distribution of the enzyme [8]. Currently no information is available regarding the cell-specific expression of HNMT in porcine and human tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Part of the permeation pathway, however, can be assumed to be transcellular. This can be concluded from the facts that a) catabolism, at least by HMT, is essentially localized within gastrointestinal epithelial cells [35,36] and that b) the sm fl uxes of hist-rad (Fig. 3) or histamine (see results: "Epithelial permeation of exogenous histamine") exceeded their corresponding ms fl uxes.…”
Section: Discussionmentioning
confidence: 92%